On quasi-Armendariz properties on skew polynomial rings - Pourtaherian, Hamideh; Rakhimov, Isamiddin Sattarovich (AIP Publishing, 2013)
This paper deals with the quasi-Armendariz ring in general setting. We generalize the notions of quasi-Armendariz and α-skew Armendariz ring to quasi α-Armendariz and quasi α-skew Armendariz ring and investigate their properties. The notions of quasi α-Armendariz and quasi α-skew Armendariz rings are useful in understanding the relationships between annihilators of rings R and R[x;α].